The relationship between salinity and pond area in the Mahakam Delta, East Kalimantan - Rizal, Samsul; Hutabarat, Johannes; Anggoro, Sutrisno; Prayitno, Slamet Budi (Faculty of Fisheries and Marine Science, Mulawarman University, 2025)
This study aims to analyze the relationship between salinity and the extent and type of mangrove vegetation in ponds within the Mahakam Delta, East Kalimantan. Sampling was conducted in ponds with different salinity levels: 0–10 ppt, 11–20 ppt, and 21–30 ppt, with each salinity category represented by 10 pond plots. Data analysis was performed using linear regression. The results showed a strong relationship between salinity variation and pond area, with an r-value of 0.630. The extent of pond expansion is related to the original mangrove type present in the pond area. This information can be used as a basis for determining suitable aquatic species for cultivation based on salinity levels. In other words, the selection of aquatic species for cultivation can be adjusted according to the appropriate pond area. Further research is needed to determine whether other factors influence the relationship between salinity levels and pond area in the Mahakam Delta region.